Phospholipase C zeta: a hidden face of sperm for oocyte activation and early embryonic development - Soukaina Azil; Modou Mamoune Mbaye; Noureddine Louanjli; Bouchra Ghazi; Moncef Benkhalifa (Korean Society of Obstetrics and Gynecology, 2024)
Oocyte activation is a fundamental event in mammalian fertilization and is initiated by a cascade of calcium signaling and oscillation pathways. Phospholipase C zeta (PLCζ) is involved in modulating cortical granule exocytosis, releasing oocyte meiotic arrest, regulating gene expression, and early embryogenesis. These processes are considered to be initiated and controlled by PLCζ activity via the inositol-1,4,5-triphosphate pathway. The decrease or absence of functional PLCζ due to mutational defects in protein expression or maintenance can impair male fertility. In this literature review, we highlight the significance of PLCζ as a sperm factor involved in oocyte activation, its mechanism of action, the signaling pathway involved, and its close association with oocyte activation. Finally, we discuss the relationship between male infertility and PLCζ deficiency.